ANALISIS STRATIGRAFI KRONOLOGI HUNIAN SITUS LOYANG UJUNG KARANG, ACEH TENGAH - Taufiqurrahman Setiawan (BRIN, 2014)
This paper tries to describe the chronolgy of settlement in Loyang Ujung Karang site by using stratigraphic data from excavation data in 2010, 2011, and 2012, to correlate it with the archaeological data, five human remains found from different burial systemand radiocarbon dating results.From the pottery, human remains, leaf casting and woven rattan found in this cave showed that cave was inhabited before 4400 + 120 BP. This site was abandoned around 2590 + 120 BP because there was a flood insideÂ the cave during the rise of Lut Tawar Lake surface level.This site then reoccupied between 2590 + 120 BP until 1900 + 100 BP based on the burial remains. Further occupation could not be determinated because it is not analyzed yet. However, based on Mingâ€™s ceramicwas found, shows us that this cave was inhabited continually from 4280 BP until 200B.